A Dél-alföldi határvidékek kutatásának rövid története - Pál, Ágnes (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The border zone research has become one of the most important objectives in geographical investigations in Hungary. In the first phase of their research geographers formulated the academic problem itself; that is, whether or not border zone settlements develop differently from those settlements which are located in other parts of the country. Border zone location supposedly has an -advantageous or disadvantageous - impact on the development of a given settlement. In the next phase of the research - between 1991-1994 - empirical research was carried out. Statistical analyses and surveys through questionnaires were made in relation to the areas and settlements located in the vicinity of the Romanian-Hungarian and Serbian-Hungarian borders. This research was primarily aimed at exploring the economic relations of these settlements, and, as a result, the conclusion was drawn that in most cases border zone location is favorable when a developed region meets another relatively developed region. If the two sides of the border are both underdeveloped, that is, poverty meets poverty, or there is a considerable developmental gap between the settlements located on the two sides of the border, border zone location is only to preserve the peripheral characteristics of the given settlement.